Maternity blues: a risk factor for anhedonia, anxiety, and depression components of Edinburgh Postnatal Depression Scale. (1st December 2020) - Zanardo, Vincenzo; Volpe, Francesca; de Luca, Federico; Giliberti, Lara; Giustardi, Arturo; Parotto, Matteo; Straface, Gianluca; Soldera, Gino
Abstract: Background: Women undergo adaptive physical and psychological changes during pregnancy, which make them vulnerable to psychological disorders. Methods: This study used a prospective observational design and included concurrent validation analysis of the 16-item Maternity Blues Scale (MBS) Dutch version to determine the direction and magnitude on the Edinburgh Postnatal Depression Scale (EPDS) symptoms, including three factors, anhedonia, anxiety, and depression in 320 puerperae early after childbirth. Results: We found a statistically significant correlation between MBS and EPDS global scores (0.22, p < .001). Moreover, Negative affect was significantly correlated with the EPDS global score (0.23, p < .001), anhedonia (0.12, p < .05), and anxiety (0.25, p < .001); Positive affect with the EPDS global score (0.14, p < .05) and depression (0.13, p < .05); and Depression subscale with EPDS global score (0.15, p < .05), anhedonia (0.12, p < .05), and anxiety (0.12, p < .05), and depression (0.12, p < .05). In addition, the subgroup of women ( n = 33, 10.3%) with EPDS > 12 presented significantly higher global MBS score (2.51 ± 0.38 versus 2.26 ± 0.38, p = .01), with negative affect (2.88 ± 0.67 versus 2.62 ± 0.38, p =.04), positive affect (2.52 ± 0.69 versus 2.32 ± 0.38, p = .04), and depression (2.09 ± 0.75 versus 1.82 ± 0.36, p = .02). Conclusion: These findings together suggest that women with higher maternity blues scores may represent a distinct subgroup at increased risk of depression.